1953
DOI: 10.1111/j.1440-1819.1953.tb00599.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Amygdaloid Nuclei and Periamygdaloid Cortex. Experiments on the Influence of Their Stimulation Upon Motility of Small Intestine and Blood Pressure

Abstract: Phylogenetically, the so-called cerebral olfactory system in the wider sense seems to have morz to do with the vegetative function than as a system for somatic sensation. Concerning amygdala, Herrick assumed from his study on Amphibia that.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1957
1957
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Further, BNST sends projections to the dorsal motor nucleus of the vagus ( 48 ), the nucleus ambiguous ( 49 ), and the nucleus of the solitary tract ( 48 ), i.e., the brain centra involved in controlling gastrointestinal motility ( 10 , 50 ). Furthermore, the BNST is involved in several autonomic regulations responding to non-fear-associated stress, and it alters both blood pressure ( 51 ) and heart rate. Our data showing modulation of the BNST in response to rotavirus infection strengthens the view of BNST involvement in intestinal motility and possibly symptoms of illness.…”
Section: Discussionmentioning
confidence: 99%
“…Further, BNST sends projections to the dorsal motor nucleus of the vagus ( 48 ), the nucleus ambiguous ( 49 ), and the nucleus of the solitary tract ( 48 ), i.e., the brain centra involved in controlling gastrointestinal motility ( 10 , 50 ). Furthermore, the BNST is involved in several autonomic regulations responding to non-fear-associated stress, and it alters both blood pressure ( 51 ) and heart rate. Our data showing modulation of the BNST in response to rotavirus infection strengthens the view of BNST involvement in intestinal motility and possibly symptoms of illness.…”
Section: Discussionmentioning
confidence: 99%
“…Pupil dilation and piloerection have already been mentioned. Respiration, heart rate, and blood pressure have been studied in the rat, rabbit, cat, dog, monkey, and human (Anand & Dua, 1956b;Andy, Bonn, Chinn, & Allen, 1959;Baldwin, Frost, & Wood, 1954;Chapman et al, 1954;Gastaut, 1952;Hilton & Zbrozyna, 1963;Kaada, 1951;Koikegami et al, 1957;Koikegami, Kimoto, & Kido, 1953;MacLean & Delgado, 1953;Naquet, 1953Naquet, , 1954Turner, 1954;Ursin & Kaada, 1960a;Wood, Schottelius, Frost, & Baldwin, 1958). Here again, the exact nature of the response varies considerably.…”
Section: Fear Rage and Arousalmentioning
confidence: 99%
“…The other major endocrine effect is for the stimulation to cause an increase in gastric secretions (Anand & Dua, 1956c;Sen & Anand, 1957;Shealy & Peele, 1957). Gastric and intestinal movements may be either increased or decreased (Eliasson, 1952;Gastaut, 1952;Koikegami, Kimoto, & Kido, 1953;Koikegami, Kushiro, & Kimoto, 1953;Shealy & Peele, 1957). Repeated amygdaloid stimulation has been shown to cause gastric bleeding and ulceration of the gastroduodenal junction (Sen & Anand, 1957).…”
Section: Fear Rage and Arousalmentioning
confidence: 99%
“…Several animals also showed ulcers and hemorrhages. It was suggested that these pathological effects might be mediated by hypothalamic mechanisms (Sen & Anand, 1957), and, in fact, several studies have shown that stimulation of the stria terminalis and the ventral amygdalofugal (and amygdalopetal) pathway also have produced gastrointestinal alterations (Hess, 1954;Koikegami, Kimoto, & Kido, 1953).…”
mentioning
confidence: 99%